Um forte holandês em Itamaracá: história e atrativo turístico pernambucano. - Lima Neto, Vicente Paulino de (2022)
Recognizing the importance of History for tourist studies on the Island of Itamaracá brought the need to analyze the reminiscence of the Brazilian colonial period in this island region, branched out among the Portuguese, French and Dutch traces referring to the defensive strongholds built on the north coast of Pernambuco, highlighted, the historical heritage of Fort Orange. Pointed out by historians as a unifying piece and with the potential to bring identity, a historical heritage must be included in the culture of different societies, being an important cultural component, within a dynamicity. In this context, European interventions, from the colonial period, are mixed with the cultural impact of native peoples and formed a valuable patrimonial, historical and cultural collection on the Island, in which Forte Orange, emerges, within a historical context, presenting a significant potential tourist attraction. Since cultural heritage is an element, it must be associated with a historical and social past, not isolating the good from its context, but creating subterfuges that can “preserve” it in the collective memory or in a space. In this line of analysis, the report highlights the need to point out the importance of the Fort's history and tourist potential, especially when the space was closed for eight years for renovations (2010-2018). After the last change in the structure (2018), no significant exploration was identified for a possible tourist rise, regarding the historical path of the construction of the Fort and its importance in the period in which it was used as a defensive stronghold. The purpose of this research was to produce a booklet aimed at elementary school students and the local community, extolling the tourist potential of the fort, with the constructive elements, its reforms and the curiosities that tell the story of Fort Orange.